MORAL CONFLICT AND AESTHETIC FREEDOM: A STUDY OF CONTEMPORARY MUSIC PHILOSOPHY FROM THE PERSPECTIVE OF IMMANUEL KANT AND FRIEDRICH NIETZSCHE - Saragih, Kantri Sajojo (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2025)
The evolution of contemporary music has created a tension between universal moral demands and artistic expressive freedom. This study analyzes this dialectic through the philosophical lenses of Immanuel Kant and Friedrich Nietzsche. Kant emphasizes aesthetics as a universal experience bound by morality, while Nietzsche liberates art from traditional conventions in favor of transgressive creative expression. The research examines radical works such as 4'33" (John Cage) and atonal music (Schoenberg) as rejections of classical aesthetic norms. The findings demonstrate that contemporary music becomes an arena for clashing values between Kantian moral order and Nietzschean deconstruction of traditional values. This conflict reflects the modern cultural dilemma of either maintaining universal principles or embracing boundless creative freedom. Using a qualitative philosophical approach, this study highlights contemporary music's dual role as both social critique and aesthetic experiment that transforms artistic paradigms.